WORKSHOP PENYUSUNAN PERANGKAT AJAR PEMBELAJARAN BERBASIS RISET - Nessy Pattimukay; Widya Putri Ramadhani (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
One effective learning model for problem-solving is the research-based learning (RBL) model. The RBL model emphasizes active student participation in the research process and enables students to conduct organized investigations to address real-world problems. Pattimura University Laboratory School is a school that organizes learning with a primary focus on research. Based on observations and interviews with the principal and teachers at Pattimura University Laboratory School, it was found that most teachers do not clearly understand RBL, resulting in teachers having difficulty designing and integrating research activities into learning materials. Therefore, strengthening and training on research-based learning is necessary. One form of intervention that can be done to address this problem is to hold a workshop on developing research-based learning teaching materials. The target of this community service activity is elementary and junior high school teachers at Pattimura University Laboratory School. The implementation of this community service activity uses a participatory approach consisting of five main stages: preparation, material delivery, demonstration, presentation, evaluation, and follow-up. This community service activity has been very effective and successful. The overall average score was 4.39 out of 5, with a satisfaction index of 87.8%, and was categorized as very good. The workshop successfully improved teachers' conceptual understanding of PBR, built practical competency in developing research-based teaching materials, strengthened teachers' confidence in innovation, and fostered motivation to develop a research culture in schools.